Produção e composição fisico-química do leite de cabras puras e mestiças da raça Saanen no estado do Ceará - Albuquerque, Ítalo Araújo (2009)
This work aimed to evaluate the milk production rate and the chemical and physical composition of milk of pure and crossbred Saanen goats in a confinement system raised in tropical climate and to determine the influence on milk production and composition of the genetic group, type of kidding and parturition order. To evaluate the milk production were studied a total of 46 pure and crossbred Saanen with without a defined racial pattern animals - SPRD, being 25 pure Saanen goats, 17 crossed 7/8 Saanen x SPRD and nine 15/16 Saanen x SPRD during the period of november of 2007 to october of 2008. Milk was collected twice a day for the manual method, with a total of 4,362 controls. Data of daily milk production (PDL) was analyzed by the minimum squares method and the total milk production (PTL) and lactation length (DL) was estimated by regression analysis. The PDL was 1.79 ± kg/day, with significant effect (P<0.05) of the genetic group, type of kidding and parturition order. For PTL there was not significant effect of none of the variable study. Crossbred Saanen goats were more production with increase of the degree of blood however, to achieve the degree of blood 15/16, the values of production are similar to pure Saanen goats. The goat milk production increases with the parturition order decreased after the fifth lactation. To evaluate the chemical and physical composition of milk were studied a total of 35 Saanen goats and crossbred Saanen with goats without a defined racial pattern - SPRD, being 16 pure Saanen goats, 12 crossed 7/8 Saanen x SPRD and seven 15/16 Saanen x SPRD. Milk samples were collected twice a day for the manual method, with a total of 1,208 samples. The data of milk composition was estimated by minimum squares method. The means of chemical and physical milk composition was 3.03% for protein, 2.97% for fat, 8.05% for solids non fat, 11.01% for total solids, 1.028g/cm3 for density and 15.25°D for acidity with significant effect (P<0.05) of all variables study. It´s concluded that the Saanen daily milk production observed in this study was between the average found for this breed and their crossed in Brazil. The milk composition is in accordance with what it determines by the current legislation for chemical and physical composition of goat milk in Brazil being highly variable, influenced by genetic group, type of kidding and parturition order in which the fat content and acidity show the greater variation among the goat milk components in the different genetics groups studied.